Efficient identification scheme in standard model based on bivariate function hard problem - Tea, Boon Chian (2014)
The existence of zero knowledge in authentication and identification has become important in cryptography due to the usefulness in authenticating and identifying honesty of both the prover and verifier without relaying any private message in communication. Many identification schemes have been set up, utilizing different assumptions in terms of hardness of the problems including RSA-problem, discrete log problem as well as the lattice problem. Even though many schemes are developed from time to time, the assurance on the scheme‟s security is important in order to prevent from being impersonated by any unauthorized and cheating parties, which either passively or actively attack the scheme. Recently, the Diophantine Equation Hard Problem (DEHP) was proposed. With the advantage that this problem only involves simple addition and multiplication operation, it has the potential to be utilized in designing a new identification scheme in the standard model and is more desirable compared to the selected well-known schemes due to its high efficiency of time computation. The new scheme is proposed based on a specific problem of DEHP, that is the Bivariate Function Hard Problem (BFHP) and is proven to be secured against impersonation under passive, active and concurrent attacks, under the assumption that solving the DEHP is hard. Analysis of computation complexity also shows that the newly designed scheme is more efficient than selected well-known existing identification schemes.